Viscous Plane Symmetric String Cosmological Model In f (R ) Gravity - Dabre, A.; Makode, Pallavi
In this paper, we have used the Plane Symmetric LRS Bianchi type I metric to study bulk viscous fluid coupled to a string of clouds within the framework of the f (R ) theory of gravity.
Keywords: Astrophysics